PENGARUH STORE IMAGE TERHADAP STORE LOYALTY MELALUI STORE SATISFACTION DALAM KEGIATAN BELANJA KONSUMEN - MIFTACHUR ROCHMAH (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2018)
This research check to regarding influence store image to store loyalty by store satisfaction in consumen shop activity in shop SHAFA moslem Gresik. Responder the checked is consumer visited and consumer buying in shop SHAFA.Intention of this research is to know influence store image to store loyalty by store satisfaction in consumen shop activity in shop SHAFA moslem Gresik. Hypothesis which is researcher formulate in this research is store image to store loyalty and store satisfaction by parsial.Analytical tool that is used to use path analysis with the help spss/.windows.v.15. The calculation result shows that three variables included in the analysis have influence significant to store loyalty by store satisfaction in consumen acitivity.This conculsion is based on the results calculation which shows the results calculated t perhitungan > t table. Results analysis path Y2 = 0,043 + 0,215X1 and Y1 = 0,111 + 0,872 X1 + 0,119 Y2 + 0,678 X1Y2. This shows that store image work partially have influence to store loyalty by store satisfaction.